Mimetic Plato: Socrates’ ethopoeia and philosophical knowledge (Argos, 2024)
In the framework of the current studies of theory and practice of μίμησις in Rep.of Plato, the objective is to investigate the Platonic characterization [ἠθοποιία] ofSocrates. The hypothesis is that the option for dialogue is linked to the way ofunderstanding and transmitting philosophical knowledge and that, in thisframework, the figure of the character Socrates embodies a type of know-how.For this purpose, on the one hand, the characterization in the Progymnásmata isinvestigated to show its function and the place that Plato occupies in this tradition.On the other hand, key passages from Apology and Republic I are analyzed toshed light on the narrative composition and, through it, try to account for thephilosophical task in the Socratic characterization. For the latter, we present thedistinction between Ryle and Polanyi's know that and know how.
Keywords: Mimesis; Plato; Narratology; Progymnásmata; Philosophy